Genetic Disorder Fanconi Anemia: A Model for Understand the Genomic Instability and Cancer Development - Ram Balak Mahto (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
“Genomic instability” is the hall mark of cancer. It has long been a debate whether the genomic instability is the causes of cancer or consequence of cancer. Significant amount of work has generated in the area of cell cycle and DNA damage repair for understanding the genomic instability, but how genomic instability transforms the normal cell into cancer cell is not well known. Studying rare human genetic diseases often leads to a better understanding of normal cellular functions. Fanconi anemia rare model disease cause genomic instability and cancer susceptibility syndrome. Fanconi kids are born normal except some kinds of congenital defects like bone marrow failure and other developmental defects, but when they are getting older (teen age) they become susceptible to all kinds of cancer.